Lethal activity of BRD4 PROTAC degrader QCA570 against bladder cancer cells - Wang, Qiang; Li, Baohu; Zhang, Wenkai; Li, Zhuoyue; Jiang, Bo; Hou, Sichuan; Ma, Shumin; Qin, Chong (Frontiers in Chemistry, 2023)
Bladder cancer is the most common malignancy of the urinary system. Efforts to identify innovative and effective therapies for bladder cancer are urgently needed. Recent studies have identified the BRD4 protein as the critical factor in regulation of cell proliferation and apoptosis in bladder cancer, and it shows promising potential for pharmacologic treatment against bladder cancer. In this study, we have evaluated the biological function of QCA570, a novel BET degrader, on multiple bladder cancer cells and explore its underlying mechanisms. QCA570 potently induces degradation of BRD4 protein at nanomolar concentrations, with a DC50 of ∼ 1 nM. It decreases EZH2 and c-MYC levels by transcriptional suppression and protein degradation. Moreover, the degrader significantly induces cell apoptosis and cycle arrest and shows antiproliferation activity against bladder cancer cells. These findings support the potential efficacy of QCA570 on bladder cancer.